Gender, family status and health characteristics: Understanding retirement inequalities in the Chilean pension model. - PARADA‐CONTZEN, Marcela (International Labour Review, 2023)
This paper aims to measure the impact of life‐cycle events on accumulated retirement savings within the context of a retirement system with mandatory individual savings accounts. Taking into account the impact of lifetime events through multiple channels, the author presents a set of correlated equations that capture labour market behaviour, portfolio and savings decisions, risk preferences, and family and health characteristics, using data from an iconic Chilean experiment. The findings indicate that a woman located in the middle of the wealth distribution who is married with two children, and who suffers a health shock in the last ten years of her working life cycle, accumulates less wealth than her counterpart.